Russian gas and European energy security - Roland Götz (Stiftung Wissenschaft und Politik (SWP), 2007)
While in the seventies gas from Russia had been regarded as a safe alternative to the energy imports from the Middle East, a newly inflamed discussion gives the impression that Russian power endangers European energy security. The procurement of natural gas by pipelines admittedly offers nearly no possibilities to change suppliers and therefore an interruption of deliveries would have considerable consequences for consumers. But the dependency is two-sided: Neither the supplier nor the recipient can change its partners. Therefore, a discontinuation of deliveries is detrimental to both sides.The endeavours of the EU to create a "southern gas corridor" (the "Nabucco" project) reveal the limitations and weaknesses of the European energy foreign policy. Europe and Russia are reacting reciprocally to perceived threats, thus creating still more threat perceptions on both sides. They find themselves in a "perception trap", which has caused a "diversification race" between the EU and Russia. At the same time, both sides are ignoring that the choice between different pipeline routes should be the task of the interested companies, which have to balance profitability and risk, in spite of political wishes. Therefore, the EU Commission's current practice of identifying priorities for new transport infrastructure and formulating them as quasi-governmental projects should be questioned.The future of the Russian gas supply capability depends primarily on the speed of development of the Yamal gas deposits. Even though Europeans can not influence this process, they can demand more transparency about Gazprom's investment plans. Likewise, this should become a topic of the EU-Russia energy dialogue. The EU external policy should concentrate on mutual information and the launch of concrete and far-reaching energy efficiency projects. (SWP Research Papers)
Keywords: 320; Russische Föderation; Inlandsmarkt